Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region, South Peru, and a description of its new subspecies, from Cotahuasi canyon, South-Central Peru - Kir’yanov, Alexander V. (Zootaxa, 2019)
A new species of the genus Colias Fabricius from the Arequipa region of Peru, C. misti Kir’yanov sp. nov., stat. nov., is established by raising it from the subspecies rank, C. lesbia misti Kir’yanov 2017. This taxonomic act is justified after detailed comparison of C. misti with representatives of phenotypically similar other South American Colias, including the subspecies of C. lesbia. The newly presented taxa are diagnosed by adult morphology, bionomics, and male genitalia. The diagnosis of a new subspecies Colias misti ccota Kir’yanov ssp. nov., discovered in the World’s deepest canyon Cotahuasi (Peru), is based on different and stable characters in phenotypes, genitalia, and bionomics of C. misti ccota and C. misti misti. Both subspecies of C. misti are endemic to the Western slopes of the Andes. It is also demonstrated that the shape of the male aedeagus is diagnostic for a reliable identification of the South American Colias.